2009
DOI: 10.1152/ajpendo.90821.2008
|View full text |Cite
|
Sign up to set email alerts
|

Glucagon-mediated impairments in hepatic and peripheral tissue nutrient disposal are not aggravated by increased lipid availability

Abstract: Glucose, fat, and glucagon availability are increased in diabetes. The normal response of the liver to chronic increases in glucose availability is to adapt to become a marked consumer of glucose. Yet this fails to occur in diabetes. The aim was to determine whether increased glucagon and lipid interact to impair the adaptation to increased glucose availability. Chronically catheterized well controlled depancreatized conscious dogs (n = 21) received 3 days of continuous parenteral nutrition (TPN) that was eith… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 35 publications
1
4
0
Order By: Relevance
“…NEFA is the major fuel oxidized by the liver and can modulate the suppression of glucose production by insulin. Our recent work indicates NEFAs interact with glucagon to impair NHGU during TPN[21]. In the present study, NEFA uptake and fractional extraction by the liver were increased, despite only modest changes in circulating NEFA concentrations.…”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…NEFA is the major fuel oxidized by the liver and can modulate the suppression of glucose production by insulin. Our recent work indicates NEFAs interact with glucagon to impair NHGU during TPN[21]. In the present study, NEFA uptake and fractional extraction by the liver were increased, despite only modest changes in circulating NEFA concentrations.…”
Section: Discussionsupporting
confidence: 49%
“…Infusion catheters were placed in the splenic vein for insulin and/or glucagon administration and in the inferior vena cava (IVC) for delivery of nutritional support. Flow probes (Transonic Systems, Ithaca, NY) were placed in the left common iliac vein with the tip positioned distal to the anastomosis with the IVC and in the abdominal aorta via the right external iliac artery [19, 21]. …”
Section: Methodsmentioning
confidence: 99%
“…Thus, the earliest studies reported quite high activity of hepatic GK, about 45 mU/mg protein in the fasted state. However, more recent studies do not agree with these results, and situate the GK activity in two different ranges: either about 10 mU/mg protein ( 126 ) or 10–15 μU/mg protein ( 135 ) . While these differences are probably related to the experimental conditions rather than to the activity assessing method, further studies should be developed in order to better characterise this enzyme in the dog.…”
Section: Glucokinase In Mammalsmentioning
confidence: 85%
“…Chronic administration of TPN augments the liver's capacity to take up glucose and metabolize it to lactate [31,35], however infection [36] and even very small increases in glucagon during stress [37] can have profound long‐term effects on the liver, lowering its ability to dispose of carbohydrate during TPN. In addition, it has been suggested that glucagon can chronically impair insulin stimulated muscle glucose disposal during nutritional support, probably via an indirect mechanism [38]. Thus, hyperglycemia, aggravated by both infection and glucagon, is a common complication of TPN administration [31].…”
Section: Glucagon's Effect During Injury or Infectionmentioning
confidence: 99%